Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1080/09637486.2016.1198892
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of green tea polyphenol EGCG((−)-epigallocatechin-3-gallate) on the proliferation of gastric cancer cells by suppressing canonical wnt/β-catenin signalling pathway

Abstract: (-)-Epigallocatechin-3-gallate (EGCG), the major polyphenol in green tea, could affect carcinogenesis and development of many cancers. However, the effects and underlying mechanisms of EGCG on gastric cancer remain unclear. We found that EGCG significantly inhibited proliferation and increased apoptosis of SGC-7901 cells in vitro. The decreased expressions of p-β-catenin(Ser552), p-GSK3β(S9) and β-catenin target genes were detected in SGC-7901 cells after treated by EGCG. XAV939 and β-catenin plasmid were furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…EGCG can inhibit cell proliferation through multiple ways in many types of cancer cells. It inhibits cell proliferation in human bladder cancer SW-780, breast cancer MDA-MB-231 and NSCLC A549 cells, and inhibits tumor growth in gastric cancer SGC-7901 xenograft mice [89,94,95]. It also induces apoptosis in human oral cancer KB, head and neck cancer FaDu, NSCLC A549, and breast cancer MCF-7 cells [96,97].…”
Section: Epigallocatechin Gallate (Egcg)mentioning
confidence: 99%
See 1 more Smart Citation
“…EGCG can inhibit cell proliferation through multiple ways in many types of cancer cells. It inhibits cell proliferation in human bladder cancer SW-780, breast cancer MDA-MB-231 and NSCLC A549 cells, and inhibits tumor growth in gastric cancer SGC-7901 xenograft mice [89,94,95]. It also induces apoptosis in human oral cancer KB, head and neck cancer FaDu, NSCLC A549, and breast cancer MCF-7 cells [96,97].…”
Section: Epigallocatechin Gallate (Egcg)mentioning
confidence: 99%
“…EGCG possesses various biological effects including anti-obesity and anti-hyperuricemia, anti-oxidative, anti-viral, anti-bacterial, anti-infective, anti-angiogenic, anti-inflammatory and anti-cancer activities [80][81][82][83][84]. It is reported to present anti-cancer effects in variety of cancer cells, including lung, colorectal, prostate, stomach, liver, cervical, breast, leukemia, gastric, bladder cancers [85][86][87][88][89][90]. Among its anti-cancer activities, EGCG exhibits multiple pharmacological actions, including the suppression of cell growth, proliferation, metastasis and angiogenesis, induction of apoptosis, and enhancement of anti-cancer immunity [85,86,[91][92][93][94].…”
Section: Epigallocatechin Gallate (Egcg)mentioning
confidence: 99%
“…In the present study, EGCG was demonstrated to suppress the viability of esophageal cancer Eca109 and Ec9706 cells via inducing apoptosis in an EGCG dose-dependent manner. EGCG has been reported to induce cancer cell apoptosis through different pathways involving the pro-oxidant, epigenetic modulation of apoptosis-related genes, including human telomerase reverse transcriptase, and to reduce cell proliferation through the modulation of cell cycle progression (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…VEGF) and apoptosis (e.g. P53 , BAX , BCL2 , caspase 3; Sur & Panda, ; Yang, Du, & Yang, ). To the best of our knowledge, no direct evidence has shown that EGCG modulates WNT/JNK pathway in tumour cells.…”
Section: Discussionmentioning
confidence: 99%